The Constitutional Court Law Reconstruction of Indonesia: The Rights & Obligations of Lawmakers in Judicial Review - Hafizh Aulia Rahman; Wicipto Setiadi (Jurnal Daulat Hukum, 2025)
This study discusses the reconstruction of the Constitutional Court Law of the Republic of Indonesia, particularly regarding the rights and obligations of the law-making institutions in the judicial review process. The main focus of this study is on the need to reformulate the norms in Article 54 of Law Number 24 of 2003, which is currently optional, to be imperative, so that the law-making institutions (the House of Representatives and the President) have a legal obligation to be present and provide information in the process of reviewing laws at the Constitutional Court. This research uses a normative juridical method with a legislative, conceptual, historical, and philosophical approach. The results of the study show that the absence of explicit regulations has weakened the principle of legislative accountability in the Indonesian constitutional law system. The proposed reformulation, in the form of the addition of Article 54A to the Constitutional Court Law, aims to strengthen the principles of checks and balances, audi et alteram partem, and due process of law in constitutional adjudication. Thus, this study provides theoretical and practical contributions to strengthening the accountability of law-making institutions and the effectiveness of judicial review in Indonesia.